2013
DOI: 10.1364/oe.21.028334
|View full text |Cite
|
Sign up to set email alerts
|

Stability of EUV multilayer coatings to low energy alpha particles bombardment

Abstract: Future solar missions will investigate the Sun from very close distances and optical components are constantly exposed to low energy ions irradiation. In this work we present the results of a new experiment related to low energy alpha particles bombardments on Mo/Si multilayer optical coatings. Different multilayer samples, with and without a protecting capping layer, have been exposed to low energy alpha particles (4keV), fixing the ions fluency and varying the time of exposure in order to change the total do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The EUV 2nd order Bragg peak reflectivity decreases from 0.48 to 0.40 and from 0.6 to 0.58 respectively for sample CL1 and sample CL2. This is consistent with near normal reflectivity measurements performed at 30.4 nm and reported in [21] for same MLs. The relative changes in reflectivities due to irradiation are very different for the two samples: CL1 lose more intensity than CL2.…”
Section: Resultssupporting
confidence: 93%
“…The EUV 2nd order Bragg peak reflectivity decreases from 0.48 to 0.40 and from 0.6 to 0.58 respectively for sample CL1 and sample CL2. This is consistent with near normal reflectivity measurements performed at 30.4 nm and reported in [21] for same MLs. The relative changes in reflectivities due to irradiation are very different for the two samples: CL1 lose more intensity than CL2.…”
Section: Resultssupporting
confidence: 93%
“…A particular case is instead that of multilayer (ML) stacks for the EUV. Several studies have demonstrated that protons and alpha particles with energy of a few keV can already lead to dramatic degradations of performance with fluences in the order of 10 16 ions/cm 2 [119][120][121]. For example, Mo/Si structures with different capping layers were irradiated by protons at 1 keV with fluences of 9•10 15 and 36•10 15 p/cm 2 , showing a change in the peak position and a degradation of the reflectance (Figure 4a).…”
Section: Charged Particlesmentioning
confidence: 99%
“…Such effect was attributed to the blistering, expansion and delamination and occurring in the topmost layers of the ML stack (see the TEM image reported in Figure 4b) [115][116] [117]. After He + ion irradiation with fluences of 2.5•10 15 ions/cm 2 , 5•10 15 ions/cm 2 10 16 ions/cm 2 the exposed MLs show a drop of reflectance but no appreciable reflectance peak shifts [109]. In this case, the degradation was attributed to an increase of the intermixing at the interfaces in the topmost layers.…”
Section: Charged Particlesmentioning
confidence: 99%